The University-Science Model and Global Megascience: 100 Years of Advancing Research - Baker, David; Powell, Justin (International Higher Education, 2025)
<h3 id="global-megascience-highlights-the-transformative-role-of-universities-in-driving-global-knowledge-production-through-collaborative-scientific-networks-rooted-in-the-twentieth-century-educational-revolution-and-the-global-diffusion-of-the-university-science-model-universities-evolved-into-pivotal-research-hubs-reshaping-science-beyond-national-borders-since-1900-scientific-output-and-collaboration-have-accelerated-across-disciplines-and-regions-exemplifying-how-research-networks-advance-discovery-and-tackle-global-challenges-however-questions-about-the-sustainability-of-megascience-remain" data-pm-slice="1 1 []">Global megascience highlights the transformative role of universities in driving global knowledge production through collaborative scientific networks. Rooted in the twentieth-century educational revolution and the global diffusion of the “university-science model,” universities evolved into pivotal research hubs, reshaping science beyond national borders. Since 1900, scientific output and collaboration have accelerated across disciplines and regions, exemplifying how research networks advance discovery and tackle global challenges. However, questions about the sustainability of megascience remain.